IELTS and TOEFL analytical comparison - Ro'ziboyeva Dilshoda; Xolmatova Gavhar (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article provides an analytical overview of IELTS and TOEFL, comparing their structure, assessment criteria, task types, scoring, and learner suitability. IELTS offers face-to-face speaking, diverse question formats, and band-based scoring, making it suitable for learners who prefer natural communication and variety in tasks. TOEFL emphasizes computer-based integrated academic tasks with standardized scoring, catering to learners comfortable with digital testing and academic contexts. The comparison enables candidates to make informed decisions according to their strengths and goals.